Koncepcja systemu wczesnego ostrzegania - ujęcie sytuacyjne - Czarny, Anna (Early Warning System Concept - Situational Approach, 2007)
The early warning system is aimed to forecast threats to the financial condition of the enterprise, I including but not limited to its bankruptcy. The selection of methods comprising the early warning I system is conditioned on many factors, the most important of which include access to information, easy I application, and high prognostic value. Such criteria are met by, inter alia, the multi-dimensional I analysis of discrimination, which is relatively widely applied in this area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 69-78